The Effect Of Work Motivation And Discipline On Organizational Culture That Implied On The Performance Of Province Office Of Manpower Offices North Sumatera - Salman Faris; Henry Muel Simanjuntak; Syaifuddin (Junal Ilmu Manajemen, 2022)
This study aims to test and analyze whether motivation and work discipline through organizational culture affects performance. The population in this study were all employees of the North Sumatra Provincial Manpower Office. The sample in this study amounted to 86 employees of the North Sumatra Province Manpower Office. Data analysis techniques in this study used two statistical approaches, namely descriptive statistics and inferential statistics with SEM (Structural Equation Modeling) models. Data collection techniques in this study used observations, questionnaires, and literature studies. The results of this study showed that: (1) Motivation positive and significant effect on organizational culture (2) Work Discipline has a positive and significant effect on organizational culture, (3) Motivation has no significant effect on performance, (4) Work discipline has a positive and significant effect on performance, (5) Organizational Culture has a positive and significant effect on performance. significant effect on performance, (6) Motivation through organizational culture has a positive and significant effect on performance, and (7) Work Discipline through organizational culture has a positive and significant effect on performance. Based on the overall results of the study, it can be concluded that Motivation and Work Discipline have implications for Kine work through Organizational Culture